2020
DOI: 10.3390/pr8060728
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Model for Assessment of Wood Chip Quality and Mixture Ratios

Abstract: This article focuses on fuel quality in biomass power plants and describes an online prediction method based on image analysis and regression modeling. The main goal is to determine the mixture fraction from blends of two wood chip species with different qualities and properties. Starting from images of both fuels and different mixtures, we used two different approaches to deduce feature vectors. The first one relied on integral brightness values while the latter used spatial texture information. The features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Table 2 shows a list of such studies. The most relevant image-based study was conducted by Plankenbuhler et al [45], which proposed an imagebased method for wood chip quality assessment. The key objective of the study [45] was to determine the mixture ratios from blends of two wood chip species of different qualities and characteristics, as shown in Fig.…”
Section: Imagementioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows a list of such studies. The most relevant image-based study was conducted by Plankenbuhler et al [45], which proposed an imagebased method for wood chip quality assessment. The key objective of the study [45] was to determine the mixture ratios from blends of two wood chip species of different qualities and characteristics, as shown in Fig.…”
Section: Imagementioning
confidence: 99%
“…The obtained results demonstrated that the prediction accuracy of the brightness-based model (R 2 > 0.9) is greater than that of the texture-based model (R 2 > 0.8). Apart from RGB (Red Green Blue) images [45,77,78], laser scanned image [50,79] and hyperspectral images [36] have also been explored for wood chip quality control. Gillespie et al [36] combined the NIR hyperspectral imaging with chemometrics to determine the moisture content and specific energy of wood chips and achieved a prediction accuracy of R 2 = 0.94 and RMSE of 1.11%.…”
Section: Imagementioning
confidence: 99%
See 1 more Smart Citation
“…They refer primarily to the tests on the raw material as an energy product at the various stages of processing and in various applications. The experimental tests analyze the impact of chips origin due to the calorific value and exhaust fumes emission, e.g., on account of tree species [14], mixture proportions [15], an acquiring method [14,16], a drying method [17], and pollution in the event of wood chips from recycling [18]. There are also the descriptions of the methods of processing wood chips to fuels in the form of ethanol fuel [19] or concentrated pellet [20].…”
Section: Introductionmentioning
confidence: 99%
“…High-quality wood chips are usually characterized by the type of wood, volume fraction of the chip content of the non-standard size, thick chips, uniform density, absence of bark and rot (Schön et al 2019;Plankenbühler et al 2020). The quality of wood chips is also affected by the grinding process.…”
mentioning
confidence: 99%